2008
DOI: 10.1590/s0103-84782008000700022
|View full text |Cite
|
Sign up to set email alerts
|

Genotipicação de Clostridium perfringens isolados de frangos de corte através da PCR múltipla

Abstract: Clostridium perfringens (Cp) é uma bactéria aneróbica gram positiva que, além de provocar gangrena gasosa e enterotoxemia em humanos e animais, constitui-se na principal causa de enterite necrótica em aves de criações intensificadas. A identificação dos isolados foi realizada pela reação de lecitinase em ágar TSC-gema de ovo, colônias com dupla hemólise em ágar sangue desfibrinado de eqüino, coloração de Gram e provas bioquímicas. Das amostras analisadas, 171Cp foram isolados em jejuno e íleo de frangos de cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…Unfortunately, this lack of data hinders any comparisons, as there are only sporadic case reports about this microorganism (MCORIST & REECE, 1992;ASAOKA et al, 2004;HAGEN & BILDFELL, 2007;URIBE et al, 2008). The detection of C. perfringens type A corroborates previous studies involving birds and other species, including humans, as this genotype is the most commonly isolated from stool samples and from the environment (CRESPO et al, 2007;GOMES et al, 2008;VAN ASTEN et al, 2010;SIQUEIRA et al, 2012). The absence of strains positive for the enterotoxin-encoding gene (cpe) is Ciência Rural, v.44, n.3, mar, 2014. not surprising because these strains are rarely found in avian samples (CRESPO et al, 2007;GOMES et al, 2008) although they are common in isolates from dog and human feces (MARKS et al, 2011;SANZ et al, 2011;SILVA et al, 2013b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Unfortunately, this lack of data hinders any comparisons, as there are only sporadic case reports about this microorganism (MCORIST & REECE, 1992;ASAOKA et al, 2004;HAGEN & BILDFELL, 2007;URIBE et al, 2008). The detection of C. perfringens type A corroborates previous studies involving birds and other species, including humans, as this genotype is the most commonly isolated from stool samples and from the environment (CRESPO et al, 2007;GOMES et al, 2008;VAN ASTEN et al, 2010;SIQUEIRA et al, 2012). The absence of strains positive for the enterotoxin-encoding gene (cpe) is Ciência Rural, v.44, n.3, mar, 2014. not surprising because these strains are rarely found in avian samples (CRESPO et al, 2007;GOMES et al, 2008) although they are common in isolates from dog and human feces (MARKS et al, 2011;SANZ et al, 2011;SILVA et al, 2013b).…”
Section: Discussionsupporting
confidence: 84%
“…Despite the large number of samples, C. perfringens was found in only a few animals, raising the possibility that it is not commonly part of the microbiota of these three families, in contrast with domestic avian species (CRESPO et al, 2007;GOMES et al, 2008). This suspicious are stronger to Cracidae once the isolation frequency of this group were lower than for Tinamidae and Ramphastidae (P<0.001).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast Gomes et al (2008), in a national study, reported the presence of C. perfringens in 68.4% of the samples from a slaughterhouse in Pará de Minas-MG.…”
Section: Resultsmentioning
confidence: 87%
“…Several papers in literature report on the frequency of this microorganism in the intestines of birds (CRAVEN et al, 2001;DE CESARE et al, 2009;GOMES et al, 2008;MANFREDA et al, 2006;SVOBODOVÁ et al, 2007;TSCHIRDEWAHN et al, 1991), but there are only few studies in Brazil on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…favoreçam o crescimento e a produção em doses elevadas das toxinas clostridiais (GOMES ET AL, 2008). Esse microrganismo, especialmente os tipos A e C, é responsável pela enterite necrótica, doença bacteriana que em infecções subclínicas, provoca redução na absorção dos nutrientes e, conseqüentemente, menor ganho de peso e piora na conversão alimentar (SCHOCKEN-ITURRINO & ISHI, 2000).…”
unclassified